(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
This research was conducted to study the variation among some Ocimum species grown in Sudan on basis of the essential oil content of their leaves and flowers and oil profiles.Three different plant materials were used in this experiment i.e. O. americanum (lime), O.basilicum( green) and O.basilicum (Egyptian). The layout of the experiment was Randomized Complete Block Design with three replicates; treatments were the three Ocimum species.The highest oil content of leaves (1.2%) was obtained from O. americanum L. (Lime) and O.basilicumL. (Green), while the lowest oil content of leaves (1 %) was obtained from O.basilicumL. (Egyptian). The highest oil content of flowers (1.7%) was obtained from O. basilicum L. (Green), while the lowest oil content of flowers (1 %) was obtained from O. americanum L. (Lime). Linalool was the most predominant component in leaves’ and flowers’ oil of Ocimumspp. followed by Eugenol and Eucalyptol (Cineole). Other important components wereCitral, Neral (β-Citral),Caryophyllene,α-Bergamotene, β-Cadinene(-), α-Caryophyllene (Humulene), β-elemene and GermacreneD. Oxygenated monoterpenes were the most predominant components in the oils followed by sesquiterpene hydrocarbons and phenylpropanoids